ANALISIS PENGARUH EMPLOYEE ENGAGEMENT AND SELF EFFICACY TERHADAP KINERJA KARYAWAN PADA PT. GLOBAL HEATERINDO TEKNIK - HEMMY FAUZAN; NOFRIANTO NOFRIANTO; FAHMI ILMAN (Maqdis: Jurnal Kajian Ekonomi Islam, 2021)
This study aims to analyze the effect of employee engagement and self-efficacy on employee performance. The method used a survey questionnaire and used multiple regression analysis using SPSS 25, the sampling method used was the census method. The results of this study indicate the influence of employee engagement and self-efficacy has a significant effect on the performance of employees of PT. Global heaterindo engineering. It can be said that the regression model used is good because almost all the variables used are able to explain the variation in the dependent variable used.